Experimental characterisation of the wake behind paired vertical-axis wind turbines. Issue 206 (November 2020) - Vergaerde, Antoine; De Troyer, Tim; Muggiasca, Sara; Bayati, Ilmas; Belloli, Marco; Kluczewska-Bordier, Joanna; Parneix, Nicolas; Silvert, Frederic; Runacres, Mark C.
Abstract: Two vertical-axis wind turbines (VAWTs) benefit from a power increase when placed side by side in close proximity. To study the potential of paired VAWTs for integration in wind farms, wind tunnel wake measurements of lift-driven VAWTs are compared for isolated and three counter-rotating configurations. Because the wake of an isolated VAWT is deflected, the direction of rotation significantly influences the wake of paired VAWTs. The wake of counter-rotating VAWTs where the adjacent blades move downwind, exhibits a similar length, width and replenishment as the wake of an isolated VAWT. The wake of counter-rotating VAWTs with adjacent upwind moving blades, however, significantly differs from an isolated VAWT wake. While its wake length is similar to an isolated VAWT wake, its width and replenishment are not. Because of appealing wake characteristics, paired VAWTs exhibit unique advantages for wind farm applications, and especially for offshore floating wind farms. Highlights: Comparison of low-blockage wind tunnel wake measurements of VAWTs in isolated and paired counter-rotating configurations. The 3D-structure of the wake is measured using multihole pressure probes, from 1D till 21D behind the turbine rotor shafts. The effect of pairing VAWTs and the direction of rotation on the wake characteristics is demonstrated.